India and South Asia - Norton, James H. K. (McGraw-Hill/Dushkin Company, 2001)
This edition features an overview of South Asia and country reports for Afghanistan, Bangladesh, Bhutan, Maldives, Nepal, Pakistan, and Sri Lanka. Selected articles from the world press explore regional issues and an annotated list of World Wide Web sites guides students to additional resources. Dushkin Online is a student Web site that is designed to support Global Studies titles.